Optimization and Validation of Recombinant Serological Tests for African Swine Fever Diagnosis Based on Detection of the p30 Protein Produced in Trichoplusia ni Larvae - Pérez Filgueira, Daniel Mariano (2006)
We describe the validation of an enzyme-linked immunosorbent assay (ELISA) and confirmatory immunoblotting assays based on a recombinant p30 protein (p30r) produced in insect larvae using a baculovirus vector. Such validation included the following: (i) the scaling up and standardization of p30r production and the associated immunoassays, (ii) a broad immunological analysis using a large number of samples (a total of 672) from Spain and different African locations, and (iii) the detection of the ASF virus (ASFV)-antibody responses at different times after experimental infection. Yields of p30r reached up to 15% of the total protein recovered from the infected larvae at 3 days postinfection. Serological analysis of samples collected in Spain revealed that the p30r-based ELISA presented similar sensitivity to and higher specificity than the conventional Office International des Epizooties-approved ASFV ELISA. Moreover, the p30r ELISA was more sensitive than the conventional ELISA test in detecting ASFV-specific antibodies in experimentally infected animals at early times postinfection. Both the recombinant and conventional ELISAs presented variable rates of sensitivity and specificity with African samples, apparently related to their geographical origin. Comparative analyses performed on the sequences, predicted structures, and antigenicities of p30 proteins from different Spanish and African isolates suggested that variability among isolates might correlate with changes in antigenicity, thus affecting detection by the p30r ELISA. Our estimations indicate that more than 40,000 ELISA determinations and 2,000 confirmatory immunoblotting tests can be performed with the p30r protein obtained from a single infected larva, making this a feasible and inexpensive strategy for production of serological tests with application in developing countries.